Real talk for real teachers : advice for teachers from rookies to veterans : "no retreat, no surrender" - Esquith, Rafe (Viking, 2013)
In Real Talk for Real Teachers, Esquith tackles the three stages of life for the career teacher, and outlines both practical advice and inspiration for managing your classrooms, challenging your students, and keeping your own passions alive. Esquith's candor about the inevitable frustration and cynicism that strike at the heart of every teacher at some point offers both comfort and connection to those who experience doubt and struggle with difficult students, endless bureaucracy, and other standard pitfalls. Esquith's years of teaching have given him gems of wisdom about how to work smarter, not harder, and how to draw on those years of experience to flourish and continue growing.